Analisis Tren Kinerja Keuangan Pemerintah Provinsi DKI Jakarta Berdasarkan Rasio Apbd Tahun 2020–2024 - Dina Era Ermawati; Alifia Rosada Nibros; Ria Anggraini; Muhammad Rahman; Abdurrachman A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the financial performance trends of the Provincial Government of DKI Jakarta based on Regional Revenue and Expenditure Budget (APBD) ratios during the 2020–2024 period. The study employed a quantitative descriptive method with a case study and time-series approach. The data consisted of secondary data obtained from the audited Budget Realization Reports (LRA) of the DKI Jakarta Provincial Government for 2020–2024. Financial performance was analyzed using regional financial ratios, including the financial independence ratio, Regional Original Revenue (PAD) effectiveness ratio, financial efficiency ratio, revenue growth ratio, and expenditure harmony ratio. The results indicate a positive trend in DKI Jakarta's financial performance, reflected in the continuous increase in regional revenue, PAD, and regional expenditure. The financial independence ratio remained above 100%, indicating a very high level of fiscal independence and low dependence on central government transfers. The PAD effectiveness ratio declined in 2021–2022 due to the COVID-19 pandemic but exceeded 100% in 2023–2024. The financial efficiency ratio ranged from 92% to 96%, while expenditure remained dominated by operational spending despite a gradual increase in capital expenditure. Overall, the DKI Jakarta Provincial Government demonstrated strong fiscal capacity and maintained stable financial performance throughout the study period.